A COMPARITIVE STUDY ON EFFECTIVENESS OF TAPING WITH IONTOPHORESIS AND TAPING ALONE IN CHRONIC PLANTAR FASCITIS - Dr. Biju Chetri; Dr. U.T. Ifthikar Ali; Dr. Madhusmita Koch; Dr. Abhijit Dutta (International Journal of Physiotherapy, 2016)
Background: Plantar fasciitis is a painful condition caused by microtrauma to plantar fascia due to overuse. It is a most common cause of heel pain in runners. Various studies proved taping and Iontophoresis as effective in the treating plantar fasciitis. But there are no studies comparing the combined effect of iontophoresis with taping and taping alone in the treatment of plantar fasciitis. Methods: 50 patients suffering from plantar fasciitis who met the inclusion criteria were selected. The subjects were randomly divided into two groups i.e. Group A and Group B. Group A received taping, iontophoresis with plantar fascia stretching. Group B received taping and plantar fascia stretching. A total of 6 treatment sessions were given on alternate days over a period of two weeks for both the groups. Results: VAS and FFI scores across baseline and post intervention showed a significant improvement statistically in their mean scores between Groups A and B (P<0.05). Between group comparison of VAS and FFI scores, it showed that subject treated with Iontophoresis in combination with taping and plantar fascia stretch (Group A) had significant improvement in VAS and functional ability when compared to subjects treated with taping and plantar fascia stretching alone (Group B). Conclusion: Iontophoresis along with Taping and plantar fascia stretching gave an additional benefit when compared with Taping and plantar fascia stretching alone in reducing pain and improving function in plantar fasciitis.